2013
DOI: 10.1111/epi.12064
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and recovery from refractory status epilepticus in the intensive care unit: A 7‐year observational study

Abstract: 40-4.12; p = 0.001 and RR 2.81, 95%CI 1.59-4.96; p < 0.0001). The estimated hazard ratio of death was 3.1 (95% CI1.6-6.0; p = 0.001) for patients with HE and 1.1 (95% CI 0.5-2.3; p = 0.745) for patients with brain tumors. RSE duration and nonconvulsive status epilepticus in coma were independently associated with death (for every hour RR 1.001; 95%CI 1.00-1.002; p = 0.011 and RR 3.62; 95%CI 1.34-9.77; p = 0.005). Significance: Brain tumors and HE had high relative risks for death and were independently associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
121
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(141 citation statements)
references
References 44 publications
15
121
3
2
Order By: Relevance
“…In what is seemingly the same patient cohort, the authors previously reported that "the use of IV anesthetic drugs and mechanical ventilation may not be strongly related to outcome and should therefore be used cautiously for informed decision-making regarding treatment." 3 We support this interpretation and stress that while anesthesia presents clear risks to the patient, this must be balanced against the risks of prolonged seizure activity. The true value of the article by Sutter et al 1 is the message to take caution before initiating anesthetics.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…In what is seemingly the same patient cohort, the authors previously reported that "the use of IV anesthetic drugs and mechanical ventilation may not be strongly related to outcome and should therefore be used cautiously for informed decision-making regarding treatment." 3 We support this interpretation and stress that while anesthesia presents clear risks to the patient, this must be balanced against the risks of prolonged seizure activity. The true value of the article by Sutter et al 1 is the message to take caution before initiating anesthetics.…”
mentioning
confidence: 51%
“…Underlying etiology may be the most important outcome predictor. 3 In a previous study, we reported that the use of IVAD was not strongly related to outcome. 3 Albeit deriving from the same center, this cohort differed regarding inclusion criteria and study period.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…[35][36][37][38] In a recent study, 38 researchers found higher rates of infection and death in patients receiving anesthetic agents, even when corrected for critical medical conditions and for the refractoriness of the status epilepticus. It remains unclear whether the anesthetic agents themselves or a selection bias led to this worsened mortality.…”
Section: Antiepileptic Drugsmentioning
confidence: 99%
“…Observational SE studies have reported different rates of CIVAD prescription: 5% in Germany, 18 8% in Italy, 19 10.7% 12 in Switzerland, 22% in France, 20 and up to 31% 21 or 36% in the United States. 22 The same is true when describing treatment of refractory SE: CIVADs were used in 30% 23 and 43% 24 of patients in Switzerland, as opposed to 87.3% in the United States. 25 Three recent studies performed in the United States and Switzerland [10][11][12] have questioned the risk/benefit ratio of TC, with observational data showing an independent association with worse outcome after correction for major confounders.…”
mentioning
confidence: 96%